2020
DOI: 10.1177/1943387520962280
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of COVID-19 Social Distancing Measures Changed the Frequency and the Characteristics of Facial Injury: The Newcastle (Australia) Experience

Abstract: Study Design: A retrospective study was undertaken of a cohort of facially injured patients using matched 8-week periods: non-COVID (2019) and COVID (2020). Objective: To determine whether there were any changes to the frequency and characteristics of facial injury due to the imposition of COVID-19 social distancing measures. Methods: The primary predictor variable was an 8-week period of COVID-19 social distancing. The primary outcome variable was the sustaining of a facial injury. Demographic (age/gender) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…A number of studies from developed nations have now reported a serendipitous decrease in the incidence of maxillofacial trauma, and a change in the characteristics of facial injury, that appeared to coincide with implementation of "lockdown" legislation and social distancing. [3][4][5][6][7][8][9][10] In this current study we have shown that the rapid changes in incidence and characteristics of maxillofacial trauma that were observed during the 8 weeks of COVID-19 lockdown have not been mirrored by an equally rapid return to seasonal baseline with the dissolution of major lockdown legislation as was seen in the previously published Australian cohort. 2 In actual fact, the UK has displayed persistent deviations from baseline incidence and patterns despite a 110% increase in maxillofacial trauma admissions between the periods during and post strict COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A number of studies from developed nations have now reported a serendipitous decrease in the incidence of maxillofacial trauma, and a change in the characteristics of facial injury, that appeared to coincide with implementation of "lockdown" legislation and social distancing. [3][4][5][6][7][8][9][10] In this current study we have shown that the rapid changes in incidence and characteristics of maxillofacial trauma that were observed during the 8 weeks of COVID-19 lockdown have not been mirrored by an equally rapid return to seasonal baseline with the dissolution of major lockdown legislation as was seen in the previously published Australian cohort. 2 In actual fact, the UK has displayed persistent deviations from baseline incidence and patterns despite a 110% increase in maxillofacial trauma admissions between the periods during and post strict COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 71%
“…[12][13][14] A review of the literature on maxillofacial trauma revealed a total of 9 studies conducted across 6 countries during the peak of COVID-19. [2][3][4][5][6][7][8][9][10] These studies are summarized in Table 3. The 6 studies that included data from previous years (to establish seasonal baseline) found a significant reduction in the incidence of maxillofacial trauma of between 26% and 72.5%.…”
Section: Discussionmentioning
confidence: 99%
“…An initial study that was undertaken in our unit (conducted over an 8 week period following the enactment of COVID-19 social distancing policy) revealed a 30% decrease in the frequency of facial injury presentation when comparing this to the same period in 2019 Table 1. 3 The purpose of this current study was to extend the application of the earlier study and determine the frequency and characteristics of facial trauma presentations following the devolution of community social distancing measures.…”
Section: Discussionmentioning
confidence: 97%
“…The senior author participated in a formal study to determine whether the implementation of COVID-19 social distancing measures changed the frequency and characteristics of facial injury. 3 The presentations in 2020 were compared to the same time period in 2019 in order to account for seasonal variations that may have impacted on the circumstances of facial injury.…”
Section: Introductionmentioning
confidence: 99%
“…Maxillofacial trauma varies from region to region, but usually occurs due to fall-downs, assaults, car accidents, vehicle collisions, and sports-related injuries. The causes of trauma have changed and various countries have reported these changes [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%